2021
DOI: 10.1093/jimb/kuab053
|View full text |Cite
|
Sign up to set email alerts
|

The aminoshikimic acid pathway in bacteria as source of precursors for the synthesis of antibacterial and antiviral compounds

Abstract: The aminoshikimic (ASA) pathway comprises a series of reactions resulting in the synthesis of 3-amino-5-hydroxybenzoic acid (AHBA), present in bacteria such as Amycolaptosis mediterranei and Streptomyces. AHBA is the precursor for synthesizing the mC7N units, the characteristic structural component of ansamycins and mitomycins antibiotics, compounds with important antimicrobial and anticancer activities. Furthermore, aminoshikimic acid, another relevant intermediate of the ASA pathway, is an attractive candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Ansamycins are broad-spectrum antibiotics with antibacterial and antitumor activities. They work by inhibiting Hsp90 (Heat Shock Protein 90) in bacteria or tumor cells ( Escalante et al, 2021 ; Skrzypczak and Przybylski, 2022 ). Bhutia et al (2021) reported a significant positive correlation between ansamycin biosynthesis and Clostridium and Enterococcus abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Ansamycins are broad-spectrum antibiotics with antibacterial and antitumor activities. They work by inhibiting Hsp90 (Heat Shock Protein 90) in bacteria or tumor cells ( Escalante et al, 2021 ; Skrzypczak and Przybylski, 2022 ). Bhutia et al (2021) reported a significant positive correlation between ansamycin biosynthesis and Clostridium and Enterococcus abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoshikimic acid (ASA) and 3amino-5-hydroxybenzoic acid (AHBA) Aminoshikimate (ASA, 151) and 3-amino-5-hydroxybenzoic acid (3,5-AHBA, 152) were once thought to originate from the shikimate pathway, 279 however seminal work by the Floss and Frost groups established the alternative, but parallel, aminoshikimate (ASA) pathway. While its discovery and characterization has been the subject of previous reviews, [280][281][282] this section will briey discuss key biosyntheses and enzymes known to date involved in the biosynthesis of ASA and 3,5-AHBA in the context of the archetype ansamycin molecule, the antibiotic rifamycin, from which many of the rst biosynthetic enzymes were characterized (Fig. 50).…”
Section: Acridone Alkaloids and Avenanthramidesmentioning
confidence: 99%
“…53 The biosynthetic pathway of hydroxycinnamic acids originates from the shikimate pathway, 54 which begins with the condensation of phosphoenolpyruvate (PEP) and erythrose-4phosphate (E4P) to form 3-deoxy-D-arabinoheptose-7-phosphate (DAHP), a step catalyzed by DAHP synthase. 55 Then, 3dehydroquinate (DHQ) synthase transforms DAHP to DHQ, which is further transformed by DHQ dehydrase into 3dehydroshikimate (DHS). NADPH-dependent shikimate dehydrogenase reduces DHS to shikimic acid.…”
Section: Biosynthesis Of Hydroxycinnamic Acid Derivativesmentioning
confidence: 99%